Legal Protection and Family Resilience of Women Victims of Post-Peace Conflict in Aceh: A Study of Gender Approach - Abdullah, Munawiah; Jannah, Miftahul; Kamsani, Siti Rozaina; Mamat, Rashidah Binti; Rambely, Nor Azlah Sham Binti; Ariffin, Nurhazlina Mohd (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study seeks to examine the legal protection and resiliency of the families of Aceh's female victims of post-peace conflict. From the outbreak of war to the end of hostilities, women have been the most affected group. This study is qualitative research employing an ethnographic methodology and analyzing the data from a gender perspective. The ethnography was conducted in three different locations: Nagan Raya, Pidie, and North Aceh. Utilized data collection methods include interviews, observation, and literature review. According to the findings of the study, the government has given legal protection to female victims of armed conflict in a variety of ways, including the establishment of a legal umbrella, the creation of special institutions, the provision of support, and thorough rehabilitation. Even though this is not evenly divided, it is vital for institutions, particularly those that care for orphans, to engage in gender-sensitive, sustainable management, and collaboration. The struggle has a significant impact on the psychological, physical, economic, social, and cultural demands of women, as well as the future of their children. Despite the fact that the conflict impacts family resilience owing to the death of family members and economic hardship, from a gender perspective, families can survive and even thrive in the face of life's difficulties. The majority of them come to accept the catastrophe, and their psychological pain is exacerbated by their religious beliefs. Although others have not been able to accept and find it difficult to forget the trauma of the conflict that has occurred.